Aircraft-structure interaction study for the assessment of the reaction-time response of nuclear containment structure. (May 2022) - Sadique, M.R.; Iqbal, M.A.; Bhargava, P.
Abstract: A systematic finite element (FE) investigation has been presented in this study to basically examine the two basic constraints (deformation and curvature) in the conventional reaction-time response approach for studying the behavior of a nuclear containment structure. A coupled finite element investigation has been carried out wherein the reaction-time response of the Boeing 707–320 and Boeing 747–400 has been obtained against the rigid flat and curved targets of diameter 42 and 100 m in order to study the possible influence of curvature on the reaction-time response curve. The aircrafts were subsequently considered to hit the deformable containment of Boiling Water Reactor Nuclear Power Plant (BWR-NPP) of diameter 42 m. The effect of target deformability thus obtained in the reaction-time response has been compared with that of the one obtained against the rigid target of the same curvature. Further, the numerical as well as analytical approaches have been employed to evaluate the exact impact area at the interface of the aircraft and flat rigid target as a function of time and incidence velocity. Finally, the behaviour of BWR-NPP has been studied against Boeing 707–320 and Boeing 747–400 using the coupled approach, traditional average contact area approach and area trifurcation (fuselage, first set engines and second set engines) approach. The response of the containment thus obtained against the three approaches has been compared.